A Single Deformed Bow Shock for Titan‐Saturn System. Issue 11 (6th November 2017) - Omidi, N.; Sulaiman, A. H.; Kurth, W.; Madanian, H.; Cravens, T.; Sergis, N.; Dougherty, M. K.; Edberg, N. J. T.
Abstract: During periods of high solar wind pressure, Saturn's bow shock is pushed inside Titan's orbit exposing the moon and its ionosphere to the solar wind. The Cassini spacecraft's T96 encounter with Titan occurred during such a period and showed evidence for shocks associated with Saturn and Titan. It also revealed the presence of two foreshocks: one prior to the closest approach (foreshock 1) and one after (foreshock 2). Using electromagnetic hybrid (kinetic ions and fluid electrons) simulations and Cassini observations, we show that the origin of foreshock 1 is tied to the formation of a single deformed bow shock for the Titan‐Saturn system. We also report the observations of a structure in foreshock 1 with properties consistent with those of spontaneous hot flow anomalies formed in the simulations and previously observed at Earth, Venus, and Mars. The results of hybrid simulations also show the generation of oblique fast magnetosonic waves upstream of the outbound Titan bow shock in agreement with the observations of large‐amplitude magnetosonic pulsations in foreshock 2. We also discuss the implications of a single deformed bow shock for new particle acceleration mechanisms and also Saturn's magnetopause and magnetosphere. Key Points: During periods of high solar wind pressure, a single deformed bow shock is formed for Titan‐Saturn system We report observation of a structure consistent with SHFAs Formation of a deformed bow shock results in new particle acceleration mechanisms